Efforts to Improve the Physical Conditions of Banyuwangi Teenage and Junior Wrestling Athletes After Coronavirus Outbreak Covid-19 - Surya Adi Saputra; Rohmat Al Wafi; Tatok Sugiarto (CV Rezki Media, 2022)
Background: The decreased intensity of exercise accompanied by the absence of an exercise program aimed at maintaining physical condition during the COVID-19 outbreak caused the wrestling athletes of Camp Satria Perkasa Kedunggebang to experience a decrease in physical condition. Objectives: This study aims to improve the physical quality of 20 athletes categorized according to their teens (ages 13-16 years) and juniors (ages 17-21 years), consisting of 14 males and 6 females. Methods: The research method used is a quantitative research type within action sports research. In this sports action research, there are two cycles, and each cycle consists of 3 to 5 meetings, where each cycle consists of 4 stages, namely planning, action/treatment, observation/observation, and reflection. Results: From the results of the tests that have been carried out, many athletes have managed to improve their speed quality as much as 70% of the total athletes, 75% agility quality, 85% strength component and 75% endurance. Conclusion: That all components of the athlete's physical condition have successfully met the previously targeted success criteria.